An investigation into the neuroprotective properties of acetylsalicylic acid and acetaminophen - Maharaj, Himant (Rhodes University, Faculty of Pharmacy, Pharmacy, 2005)
The potent analgesic property of acetylsalicylic acid and acetaminophen makes these the most commonly used analgesics in the world. Easy accessibility and cost effectiveness of these agents are attractive to patients seeking pain relief. However, the abuse of nonnarcotic analgesics such as acetaminophen and acetylsalicylic acid by alcoholics and patients seeking to relieve dysphoric moods is well documented. These agents therefore impact on the brain neurotransmitter levels and therefore all processes involved in the synthesis and metabolism of neurotransmitters may be affected. The use of non-narcotic analgesics has been reported to reduce the incidence of neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD). The mode of action by which acetylsalicylic acid and acetaminophen elicit neuroprotection is however unclear as many mechanisms of action have been inconclusively postulated. The first part of this study aims to elucidate the various mechanisms by which acetylsalicylic acid and acetaminophen affect the enzymes responsible for the catabolism of tryptophan, which is a precursor for the mood elevating neurotransmitter serotonin, as well as to investigate whether these agents alter the interplay between serotonin and pineal indole metabolism. The second part of this study focuses on the neuroprotective properties of acetylsalicylic acid and acetaminophen utilizing the neurotoxic metabolite of the kynurenine pathway, quinolinic acid and the potent Parkinsonian neurotoxin, 1-methyl-4-phenylpyridinium (MPP+). The ability of acetylsalicylic acid and acetaminophen to alter TRP metabolism was determined by investigating the effects of these agents on the primary enzymes of the kynurenine pathway i.e. tryptophan 2, 3-dioxygenase and indoleamine 2,3-dioxygenase as well as to investigate whether these agents would have any effects on 3-hydroxyanthranilic acid oxygenase. 3-Hydroxyanthranilic acid oxygenase is the enzyme responsible for the synthesis of quinolinic acid. Acetylsalicylic acid and acetaminophen alter tryptophan metabolism by inhibiting tryptophan 2, 3-dioxygenase and indoleamine 2,3-dioxygenase thus increasing the availability of tryptophan for the production of serotonin. Acetylsalicylic acid and acetaminophen also inhibit 3-hydroxyanthranilic acid oxygenase thus implying that these agents could reduce quinolinic acid production. Acetaminophen administration in rats induces a rise in serotonin and norepinephrine in the forebrain. Acetylsalicylic acid curtails the acetaminophen-induced rise in brain norepinephrine levels as well as enhances serotonin metabolism, indicating that analgesic preparations containing both agents would be advantageous, as this would prevent acetaminophen-induced mood elevation. The results from the pineal indole metabolism study show that acetylsalicylic acid enhances pineal metabolism of serotonin whereas acetaminophen induces an increase in melatonin levels in the pineal gland. Neuronal damage due to oxidative stress has been implicated in several neurodegenerative disorders such as AD and PD. The second part of the study aims to elucidate and characterize the mechanism by which acetylsalicylic acid and acetaminophen afford neuroprotection. The hippocampus is an important region of the brain responsible for memory. Agents such as quinolinic acid that are known to induce stress in this area have detrimental effects and could lead to various types of dementia. The striatum is also a vulnerable region to oxidative stress and hence (MPP+), which is toxic for this particular region of the brain, was also used as a neurotoxin. The results show that ASA and acetaminophen alone and in combination, are potent superoxide anion scavengers. In addition, the results imply that these agents offer protection against oxidative stress and lipid peroxidation induced by several neurotoxins in rat brain particularly, the hippocampus and striatum. Histological studies, using Nissl staining and Acid fuchsin, show that acetylsalicylic acid and acetaminophen are able to protect hippocampal neurons against quinolinic acidinduced necrotic cell death. Immunohistochemical investigations show that QA induces apoptotic cell death in the hippocampus, which is inhibited by ASA and acetaminophen. In addition, ASA and acetaminophen inhibited MPP+ induced apoptotic cell death in the rat striatum. The study also sought to elucidate possible mechanisms by which ASA and acetaminophen exert neuroprotective effects in the presence of MPP+ as these agents are shown to prevent the MPP+-induced reduction in dopamine levels. The results show that acetylsalicylic acid and acetaminophen inhibit the action of this neurotoxin on the mitochondrial electron transport chain, a common source of free radicals in the cell. In addition, these agents were shown to block the neurotoxic effects of MPP+ on the enzymatic defence system of the brain i.e. superoxide dismutase, glutathione peroxidase and catalase. The reduction in glutathione levels induced by MPP+ is significantly inhibited by acetylsalicylic acid and acetaminophen. The results imply that these agents are capable of not only scavenging free radicals but also enhance the cell defence mechanism against toxicity in the presence of MPP+. These agents also block the MPP+-induced inhibition of dopamine uptake into the cell. This would therefore reduce auto-oxidation of dopamine thus implying another mechanism by which these agents exert a neuroprotective role in MPP+-induced neurotoxicity. The discovery of neuroprotective properties of acetylsalicylic acid and acetaminophen is important considering the high usage of these agents and the increased incidence in neurological disorders. The findings of this thesis point to the need for clinical studies to be conducted as the results show acetylsalicylic acid and acetaminophen to have a definite role to play as antioxidants. This study therefore provides novel information regarding the neuroprotective effects of these agents and favours the use of these agents in the treatment of neurodegenerative disorders, such as AD and PD, in which oxidative stress is implicated.
Keywords: Aspirin; Acetaminophen; Analgesics; Alzheimer's disease -- Treatment; Parkinson's disease